2010
DOI: 10.1016/j.nima.2010.06.361
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-gamma discrimination by pulse analysis with superheated drop detector

Abstract: Superheated drop detector (SDD) consisting of drops of superheated liquid of halocarbon is irradiated to neutrons and gamma-rays from 252 Cf fission neutron source and 137 Cs gamma source separately. The analysis of pulse height of the signals in the neutron and gamma-ray sensitive temperature provides strong information on the identification of neutron and gamma-ray induced events.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…The amplitude distribution for neutron induced events is compared with those of the gamma-ray induced events at 40.5 o C and 44.5 o C ( figure 6). Figure 6 shows that the pulses due to the neutron induced events are predominantly of higher amplitude compare to those of the gamma-ray induced events, which agrees with the earlier report [18] by Das et. al. This happens due to the fact that for neutrons the heavy recoils, with their higher LET, deposit more energy in the critical diameter compared to that deposited for gamma-rays, since the electrons deposit energy almost at the end of their track [23].…”
Section: Measurement Of Maximum Pulse Amplitudesupporting
confidence: 89%
See 1 more Smart Citation
“…The amplitude distribution for neutron induced events is compared with those of the gamma-ray induced events at 40.5 o C and 44.5 o C ( figure 6). Figure 6 shows that the pulses due to the neutron induced events are predominantly of higher amplitude compare to those of the gamma-ray induced events, which agrees with the earlier report [18] by Das et. al. This happens due to the fact that for neutrons the heavy recoils, with their higher LET, deposit more energy in the critical diameter compared to that deposited for gamma-rays, since the electrons deposit energy almost at the end of their track [23].…”
Section: Measurement Of Maximum Pulse Amplitudesupporting
confidence: 89%
“…The vaporization of a superheated droplet is associated with a change in volume and also the emission of an acoustic pulse, both of which can be detected independently by active devices [13][14][15][16]. The acoustic pulse bears some unique characteristic features, which makes SDD a good tool for discrimination of different kinds of energetic radiation [17,18]. In recent years, the study of the characteristics of the acoustic signals is one of the important topics in the superheated liquid based detector research [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Differential power (P) distribution [10] of the pulses obtained at different temperatures for 137 Cs γ-rays induced events in C 4 F 10 is shown in Fig.2. It is reported that the peak of the distribution of the integrated signal power, , for neutron induced events for C var P 4 F 10 detector depends on the temperature [11].…”
Section: Resultsmentioning
confidence: 99%
“…By varying the operating condition, using liquids of different boiling points and compositions, and employing different pulse analysis techniques, neutrons, α-particles, γ -rays etc, the unwanted backgrounds for cold dark matter search experiment, can be identified. Extensive studies have been made with R114 as the sensitive liquid for the response of neutrons and γ -rays of this type of detector [8][9][10]. C 4 F 10 is the most favoured sensitive liquid for cold dark matter search experiment for PICASSO (Project In CAnada to Search for Supersymmetric Objects) collaboration [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In case of 12 C (180 MeV/u), the deviation (∆ 2 1 ) is smallest for nucleation parameter k = 0.24. For the other two heavier ions, 20 Ne (400 MeV/u) 7,8,9 ) given by…”
Section: Simulation Imentioning
confidence: 99%